Are Exclusive e-Cigarette Users Unique? Comparing Predictors of Exclusive e-Cigarette Use with Traditional Tobacco Use and Dual Use among U.S. Adolescents. (12th May 2021) - Burnell, Kaitlyn; Kwiatek, Sarah M.; Hoyle, Rick H.
Abstract: Background: As e-cigarette use rises among U.S. adolescents, the need to understand its risk factors becomes increasingly urgent. If the risk profile of adolescents who exclusively use e-cigarettes differs from those who use traditional tobacco products and dual users, prevention and intervention efforts would need to target such differences. Methods: In a sample of 708 adolescents, this study compared individual, peer, and family risk factors that are classically associated with greater substance use between exclusive e-cigarette users and traditional tobacco product users. Results: Exclusive e-cigarette users and traditional tobacco product users share many risk factors when compared to non-users. Additional analyses compared exclusive e-cigarette users to exclusive traditional tobacco users and dual users, with some differences emerging. Lower friend (OR = 0.28, 99% CI [0.12, 0.67]) and peer e-cigarette use (OR = 0.26, 99% CI [0.13, 0.52]), and greater friend cigarette smoking (OR = 2.17, 99% CI [1.23, 3.83]) predicted higher odds of being an exclusive traditional tobacco user compared to an exclusive e-cigarette user. Lower SES (OR = 0.67, 99% CI [0.51, 0.90]), and greater friend (OR = 2.68, 99% CI [1.56, 4.59]) and peer cigarette smoking (OR = 1.91, 99% CI [1.17, 3.13]) predicted greater odds of being a dual user compared to an exclusive e-cigarette user. Conclusion : Although some differences exist between exclusive e-cigarette users and traditional tobacco users, their risk profiles are generally the same. Prevention and intervention efforts that target traditional tobacco product could guide efforts to target e-cigarette use and dual use. Supplemental data for this article is available online at https://doi.org/10.1080/10826084.2021.1899236 .